Militant Minority: British Columbia Workers and the Rise of a New Left, 1948-1972 - Isitt, Benjamin (University of Toronto Press, Scholarly Publishing Division, 2011)
[This book] tells the compelling story of British Columbia workers who sustained a left tradition during the bleakest days of the Cold War. Through their continuing activism on issues from the politics of timber licenses to global questions of war and peace, these workers bridged the transition from an Old to a New Left.In the late 1950s, half of B.C.'s workers belonged to unions, but the promise of postwar collective bargaining spawned disillusionment tied to inflation and automation. A new working class that was educated, white collar, and increasingly rebellious shifted the locus of activism from the Communist Party and Co-operative Commonwealth Federation to the newly formed New Democratic Party, which was elected in 1972. Grounded in archival research and oral history, Militant Minority provides a valuable case study of one of the most organized and independent working classes in North America, during a period of ideological tension and unprecedented material advance. --Publisher's description
Keywords: 20th century; British columbia; History; New Left; Political activity; Working class